(untitled) (قضايا سياسية, 2024)
This study discusses the possibility of a new revolutionary wave within the context of an Arab revolutionary pattern qualified to explode under the impact of political and economic factors. These factors are linked to the failures resulting from the 2011 wave, whether in terms of its failure to establish a genuine path for legal, democratic, and economic reform or the success of the political elite, which the revolutions sought to eliminate at that time, in regaining its dominance over political power before the first decade of these revolutions concluded. There are also socio-economic factors related to the chronic failure of the social policies of authoritarian regimes. These policies not only previously produced social inequality and exclusion but also continued to fail in evaluating and mitigating them after regaining power, especially after their exacerbation due to the recent global economic crises. These crises heightened the deterioration of the living conditions of Arab peoples, as broad segments of their middle class slipped into poverty, fragility, and unemployment, or found themselves on the margins of society. The study concludes that the gap between political systems and Arab peoples is widening, and the recorded decline in the social conditions of Arab peoples in their politically turbulent reality is likely to push them towards revolution once again. Consequently, reducing the social discontent that triggers revolutionary action now requires Arab systems to expedite comprehensive political, economic, and developmental reforms. Keywords : The Arab Revolutionary Paradigm - Economic and social crises - Deteriorating living conditions – Authoritarianism - A new revolutionary wave.